Synthetic Study of the Angular Tetracyclic Core Skeleton of Landmycine A via Masamune–Bergman Cyclization - Yamaguchi, Sho; Tanaka, Hiroshi; Yamada, Ryo; Kawauchi, Susumu; Takahashi, Takashi (Synlett, 2012)
We describe the synthesis, via Masamune–Bergman cyclization, of an angucycline derivative involving a quinone in the B ring and a nonaromatic hydroxylated C ring. The naphthoquinone was synthesized via the copper-catalyzed Ullmann reaction of the dihalo aryl moiety, and the subsequent oxidation of a corresponding hydroquinone. The aryl dihalide was prepared by the dihalogenation of the 1,4-diradical generated during the Masamune–Bergman cyclization of the 1,2- dialkynylbenzene under neutral conditions. This methodology suggests a new route for the construction of natural products containing an anthraquinone skeleton.
Keywords: aglycon; deoxyoligosaccharide; quinone; NHK coupling; Ullmann coupling